Hereditary alpha-tryptasemia and monoclonal mast cell disorders - Chantran, Yannick; Arock, Michel (Frontiers in Allergy, 2025)
Monoclonal mast cell disorders (mMCD), including systemic mastocytosis, are characterized by the abnormal accumulation of clonal mast cells, often leading to elevated baseline serum tryptase (bST) levels. Thus, bST evaluation is useful for the diagnosis, classification, and management of patients with mMCD. Hereditary alpha-tryptasemia (HαT) is a relatively frequent genetic trait also characterized by elevated bST levels. As compared to the general population, HαT is over-represented among patients with mMCD, and associated with even more frequent and severe mast cell activation symptoms, such as hymenoptera venom-induced anaphylaxis. Although both HαT and mMCD induce increased bST levels, their overlap in laboratory features, and potentially in associated clinical manifestations, have made the diagnostic process of mMCD more accurate but more complicated. In this review, we provide a brief overview of mMCD, the critical role played by bST in their diagnosis, and on HαT as one of the main bST level modifier. Next, we summarize the existing literature regarding the observed association between HαT and mMCD, with particular attention payed to the prevalence of HαT in patients with mMCD, and the clinical manifestations associated with HαT-positive individuals in mMCD. Finally, we discuss the evidence for and against different explanations underlying this association, focusing on HαT's possible influence on diagnostic criteria for mMCD, its potential to act as a modifier of mast cell related symptoms, and its potential role in promoting mast cell proliferation. We conclude with the diagnostic challenges that clinicians face in distinguishing HαT from other mast cell disorders, the role of bST measurement and tryptase genotyping, and propose management strategies for patients with different presentations. This review underlines the value of a comprehensive diagnostic approach to better understand and manage patients with HαT and mMCD.